Immunohistochemical expression of MGMT in Gliomas - Jalal, Jalal Ali (Cellular and Molecular Biology, 2020)
Glioma is one of the main tumors of the central nervous system occurring in the spinal cord or brain, and is the origin of glioma tumors. The most common site of glioma is the brain. Glioma accounts for 30% of all central nervous system tumors and 80% of malignant brain tumors. O6-methylguanine-DNA methyltransferase (MGMT) gene mutations have been identified in many human cancers including gliomas. This study aimed to evaluate the immune expression of MGMT in different gliomas and its relationship with different clinicopathological parameters. From January 2015 to January 2017, 97 cases of glioma were retrieved from the Rizgary Pathology Center in Erbil-Iraq. The tumors were typed and graded according to the 2007 World Health Organization Brain Tumor Classification. Immunohistochemical staining was done for MGMT using monoclonal Antibodies via the automated immunostainer technique. Positive MGMT immunoexpression was observed in 60 (61.9%) cases. Significantly high rates of MGMT immunoexpression were demonstrated among the 2 age groups: 45-54 years and 25-34 years (23.3% and 21.7% respectively). Most positive cases were observed among the supratentorial tumors (81.7%) and dominant grade IV gliomas (48.4%) with no significant association. Immunohistochemically, MGMT is frequently expressed in gliomas particularly in glioblastomas with bimodal age association.